Effects of Beeswax Coating on the Oxidative Stability of Long-Ripened Italian Salami - Marcello Trevisani; Matilde Cecchini; Daniela Siconolfi; Rocco Mancusi; Roberto Rosmini (Journal of Food Quality)
Beeswax coating of foods put a barrier to oxygen, light, and vapour that can help to prevent oxidation of fat and pigments and water loss. The amounts of 2-thiobarbituric acid reactive substances (TBARS) and water activity (Aw) were assessed in Italian salami coated with beeswax at 55 days of ripening and compared with controls at 5, 6, and 7 months of shelf life. The results were correlated with sensory quality. TBARS levels were below 0.8 mg kg−1 in the beeswax-coated salami until 6 months of aging (median 0.697, max 0.795) and significantly higher in the uncoated salami (median 1.176, max 1.227). A slight correlation between the amount of TBARS and Aw was observed in beeswax-coated salamis, whereas this effect was masked in controls by the large Aw variability observed at 7 months. Beeswax coating prevents case hardening and facilitated the peeling.